Analisis Usaha Penangkaran Benih Padi (Kasus di Subak Kusamba, Desa Karangdadi, Kecamatan Dawan, Kabupaten Klungkung) - NYOMAN RESI ARNINGSIH; I GEDE SETIAWAN ADI PUTRA; I PUTU DHARMA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2017)
Rice Seed Multification Business Analysis (A Case at Subak of Kusamba,Village of Karangdadi, Sub-District of Dawan, Regency of Klungkung)One of supporting the success of productivity is high quality seed. Efforts to increase rice production have been done by the government. One of the government's efforts is to create programs for the achievement of food self-sufficiency of rice through the Special Effort (UPSUS), and to increase the production of rice, corn and soybeans (Pajale). The purpose of this study was to find out how much the level of income received by farmers as producers of raw materials and UD Tunas Mekar as the seed breeder of rice paddy. This research was conducted at Subak of Kusamba, Karangdadi Village, Dawan Sub-District, Klungkung Regency. The total sample was as many as 30 farmers of respondents. The analytical methods used were quantitative descriptive analysis, ratio data analysis, analysis of farming, and the R / C ratio. The results showed that the income received by farmers as producers of raw materials of rice seeds was Rp 4. 279 266 with an average land area of 3,400 square meters in one cycle of planting and the R / C Ratio obtained was 2.58. Operating revenues of paddy seed multification at UD. Tunas Mekar was Rp. 113,531,016 in one production process with the R / C ratio of 1.50. The suggestion that can be given that the government is expected to provide subsidized seed that can be affordable by the farmers. The cooperation between UD. Tunas Mekar and the farmers should continue to provide assistance to farmers so that they are excited about doing their farming.